Evolutionary Analysis of the VP1 and RNA-Dependent RNA Polymerase Regions of Human Norovirus GII.P17-GII.17 in 2013–2017 - Matsushima, Yuki; Mizukoshi, Fuminori; Sakon, Naomi; Doan, Yen Hai; Ueki, Yo; Ogawa, Yasutaka; Motoya, Takumi; Tsukagoshi, Hiroyuki; Nakamura, Noriko; Shigemoto, Naoki; Yoshitomi, Hideaki; Okamoto-Nakagawa, Reiko; et al. (Frontiers in Microbiology, 2019)
Human norovirus (HuNoV) GII.P17-GII.17 (Kawasaki2014 variant) reportedly emerged in 2014 and caused gastroenteritis outbreaks worldwide. To clarify the evolution of both VP1 and RNA-dependent RNA polymerase (RdRp) regions of GII.P17-GII.17, we analysed both global and novel Japanese strains detected during 2013–2017. Time-scaled phylogenetic trees revealed that the ancestral GII.17 VP1 region diverged around 1949, while the ancestral GII.P17 RdRp region diverged around 2010. The evolutionary rates of the VP1 and RdRp regions were estimated at ~2.7 × 10−3 and ~2.3 × 10−3 substitutions/site/year, respectively. The phylogenetic distances of the VP1 region exhibited no overlaps between intra-cluster and inter-cluster peaks in the GII.17 strains, whereas those of the RdRp region exhibited a unimodal distribution in the GII.P17 strains. Conformational epitope positions in the VP1 protein of the GII.P17-GII.17 strains were similar, although some substitutions, insertions and deletions had occurred. Strains belonging to the same cluster also harboured substitutions around the binding sites for the histo-blood group antigens of the VP1 protein. Moreover, some amino acid substitutions were estimated to be near the interface between monomers and the active site of the RdRp protein. These results suggest that the GII.P17-GII.17 virus has produced variants with the potential to alter viral antigenicity, host-binding capability and replication property over the past 10 years.